Squalene epoxidase promotes the chemoresistance of colorectal cancer via (S)-2,3-epoxysqualene-activated NF-κB - Liu, Qi; Zhang, Yajuan; Li, Huimin; Gao, Hong; Zhou, Yijie; Luo, Dakui; Shan, Zezhi; Yang, Yufei; Weng, Junyong; Li, Qingguo; Yang, Weiwei; Li, Xinxiang (Cell communication and signaling, 2024)
While de novo cholesterol biosynthesis plays a crucial role in chemotherapy resistance of colorectal cancer (CRC), the underlying molecular mechanism remains poorly understood. We conducted cell proliferation assays on CRC cells with or without depletion of squalene epoxidase (SQLE), with or without 5-fluorouracil (5-FU) treatment. Additionally, a xenograft mouse model was utilized to explore the impact of SQLE on the chemosensitivity of CRC to 5-FU. RNA-sequencing analysis and immunoblotting analysis were performed to clarify the mechanism. We further explore the effect of SQLE depletion on the ubiquitin of NF-κB inhibitor alpha (IκBα) and (S)-2,3-epoxysqualene on the binding of IκBα to beta-transducin repeat containing E3 ubiquitin protein ligase (BTRC) by using immunoprecipitation assay. In addition, a cohort of 272 CRC patients were selected for our clinical analyses. Mechanistically, (S)-2,3-epoxysqualene promotes IκBα degradation and subsequent NF-κB activation by enhancing the interaction between BTRC and IκBα. Activated NF-κB upregulates the expression of baculoviral IAP repeat containing 3 (BIRC3), sustains tumor cell survival after 5-FU treatment and promotes 5-FU resistance of CRC in vivo. Notably, the treatment of terbinafine, an inhibitor of SQLE commonly used as antifungal drug in clinic, enhances the sensitivity of CRC to 5-FU in vivo. Additionally, the expression of SQLE is associated with the prognosis of human CRC patients with 5-FU-based chemotherapy. Thus, our finding not only demonstrates a new role of SQLE in chemoresistance of CRC, but also reveals a novel mechanism of (S)-2,3-epoxysqualene-dependent NF-κB activation, implicating the combined potential of terbinafine for 5-FU-based CRC treatment.